The role of Private Sector in Development of Afghanistan (International Journal of Scientific Research and Management (IJSRM), 2022)
The following research is based on the role of private sector in the development of Afghanistan. Research starts with the introductory section where the researcher has provided the background of the country along with the background of the business economy of the nation. Research aims objectives and the questions have been provided in this chapter which helps the readers to get a clear understanding of the purpose of the research. Another important addition in this chapter is the structure of the total study where researcher provides the detailed description about the contents of the research. The role of NATO and the top superpowers in the current economical and geopolitical situation in the country has been one of the major milestones in the present and future of the country. The following milestones have helped in the development of the infrastructure and rules of the country. The research questions set up in the research have all pointed directly to the topic that is based on the role the private sector industry plays in the development of the country and also the major outcomes of the developmental process. The review of the literature has concentrated on the works of the authors who have vastly written and discussed on the following sector of the country. The literary review has identified the major problems regarding the same and has also pointed out to the different types of the factors that lead to the current problems. These problems have been the major cause for the negative growth of the business organizations in the country. The methods used in the dissertation have been justified as well as explained. The use of the positivism philosophy and descriptive techniques research design along with the selection of the secondary research has been helpful for the research. The use of the theme based study has been used to get a detailed qualitative review of the following topic. The research has a wide scope and great approach just because it has presented a number of recommendations which has been a major success factor for the research.